Governos de Coalizão nas Democracias Presidencialistas e Parlamentaristas - Cheibub,José Antonio (2002)
Are government coalitions less frequent under presidentialism than under parliamentarism? The only difference be w e the two systems is that unscheduled elections are held under parliamentarism in those situations in which under presidentialism a majority legislative coalition opposes the executive. In both systems, portfolio coalitions are formed only when the formateur party and the one closest to it are relatively distant in policy terms. Otherwise, the formateur party governs alone, satisfied with the legislative outcomes. Hence, portfolio minority governments need not be less effective legislatively than coalition governments. Whatever is wrong with presidentialism, is not due to the difficulty of forming coalitions.